Modern State and Tendencies in Agricultural Land Use - Angelina O. PASHUTA; Elena V. VORONTSOVA; Maxim A. CHERNYKH; Tatiana V. CHASTUKHINA (Communications of International Proceedings, 2021)
The article offers methodological methods for diagnosing the state of agricultural land use in the Russian Federation; involving the identification of factors affecting land use. Factors aimed at improving the efficiency and rationality of land use; the main development trends, characterized by the use of a dynamic approach and allowing to get an objective idea of the situation with the composition, structure and quality of land, which can become the basis for developing practical recommendations for improving the organization of land use are considered.
Keywords: Agricultural Land; Factors Affecting Land Use; Land Use Efficiency; Rational Land Use.